Analysis of organizational structure and business process changes in construction companies under the influence of digital technologies - CHUBIN, Andrii (Ways to Improve Construction Efficiency, 2025)
The relevance of the study is determined by the increasing digitalization of the construction industry, which requires the adaptation of organizational structures and business processes to enhance the resilience of enterprises to external challenges. The absence of a unified information platform and insufficient coordination between departments pose additional risks to effective resource management. The purpose of the article is to substantiate the directions for transforming organizational structures and business processes in construction companies under the influence of digital technologies, focusing on increasing their adaptability, productivity, and resilience to external challenges. The research methodology is based on the use of system analysis methods to assess the impact of digital technologies on organizational structures, predictive modeling to identify effective data management tools, and comparative analysis to determine optimal solutions in resource management. The scientific novelty lies in the proposed comprehensive approach to the transformation of organizational structures in construction companies based on the integration of automated platforms, predictive analysis systems, and resource monitoring tools, which ensures consistency between departments and reduces the risks of overspending. The study proves that the implementation of a unified digital platform for integrating data from various departments provides centralized resource management and enhances the transparency of operational processes. It has been identified that the main problems include the lack of centralized resource monitoring, a low level of data protection in cloud systems, and insufficient readiness of personnel to use digital tools. It is concluded that the implementation of predictive analysis systems for risk assessment, automated platforms for material resource management, and tools for monitoring employee productivity will promote consistency between departments, reduce costs, and improve the effectiveness of management decisions. The prospects for further research are associated with the development of adaptive models of digital transformation for construction companies with an emphasis on integrating artificial intelligence for continuous resource monitoring, risk forecasting, and assessing the effectiveness of management decisions.